Relationship between levels of depression and sports injuries in football and indoor football players - Olmedilla Zafra, A.; Ortega Toro, E.; Murcia López, J. A.; García Angulo, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aim of this study is to determine whether there are differences in levels of depression among players injured and uninjured players. Participants were 219 football and indoor footballplayers, aged between 16 and 34 years, with a mean age of 22.07 (± 4.7). To register injuries based on the identification and registration system used by FIFA injury protocol was used; to assess depression Depression Scale DASS-21 questionnaire was used. It used a descriptive cross-sectional design. The results indicate that the injured players scored higher than uninjured in depression variable, although these differences were not statistically significant.